2019
DOI: 10.1111/hsc.12810
|View full text |Cite
|
Sign up to set email alerts
|

Understanding wellness and barriers to care among Iraqi refugee women in the United States

Abstract: Iraqi refugees in the US experience a high prevalence of non‐communicable diseases. In this article, we explore how cultural and structural realities intersect to influence utilisation of preventative healthcare and cancer screening with the aim of understanding health disparities in this population. We conducted three focus group discussions with a total of 14 Iraqi refugee women living in a northeastern US city in 2016 and analysed the qualitative data using a thematic analysis. Eight themes emerged from our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…Participants had heard about HPV and vaccination but had limited knowledge about HPV. Pap test and HPV vaccine uptake depended on doctor recommendations and receiving husband or family support .85 Ross Perfetti et al (2019) [ 61 ]; HC USA; CO Iraq Understand health and attitudes towards preventive care, including cancer screening, and how they relate to cultural and structural mediators of health Snowball sampling; Philadelphia community clinic; 3 semi-structured FGDs n = 14; refugees; < 30- > 60 yrs. ; yrs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Participants had heard about HPV and vaccination but had limited knowledge about HPV. Pap test and HPV vaccine uptake depended on doctor recommendations and receiving husband or family support .85 Ross Perfetti et al (2019) [ 61 ]; HC USA; CO Iraq Understand health and attitudes towards preventive care, including cancer screening, and how they relate to cultural and structural mediators of health Snowball sampling; Philadelphia community clinic; 3 semi-structured FGDs n = 14; refugees; < 30- > 60 yrs. ; yrs.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 28 studies, 13 were conducted in the USA [ 48 , 53 , 55 57 , 59 61 , 63 , 69 , 72 74 ], two each in Australia [ 62 , 64 ], Jordan [ 52 , 68 ], Lebanon [ 49 , 50 ] and Canada [ 70 , 71 ], one each in Congo [ 66 ], Israel [ 54 ], Netherlands [ 67 ], Pakistan [ 65 ], South Korea [ 65 ], Thailand [ 47 ] and one was a multi country study which included Bangladesh, Jordan, Djibouti, Kenya, Malaysia and Uganda [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In that study, a majority of respondents had favorable views of their healthcare but indicated that language barriers made it challenging to access care. Several factors may contribute to these barriers in accessing care, including acculturation, lack of reliable transportation, difficulty navigating the complex US healthcare system, and language and communication barriers[3-5, 32, 33].…”
Section: Discussionmentioning
confidence: 99%